Exercise Capacity Is Improved by Levosimendan in Heart Failure and Sarcopenia via Alleviation of Apoptosis of Skeletal Muscle - Wang, Di; Song, Ming; Shen, Long-fei; Han, Lu; Zhu, Ping; Jia, Xu; Shang, Guo-kai; Cao, Yuan; Zhang, Wei; Zhong, Ming; Wang, Zhi-hao (Frontiers in Physiology, 2022)
Background Patients suffering from chronic heart failure (CHF) show an increased prevalence of sarcopenia. Levosimendan is an effective drug for the treatment of heart failure, but its effect on sarcopenia is still unclear. We aimed to explore whether levosimendan could enhance skeletal muscle contractibility, improve skeletal muscle atrophy, and thus improve exercise tolerance of individuals with heart failure. Methods C57BL6/J mice were used to establish the heart failure with sarcopenia model and injected of levosimendan. Mice (n=40) were separated into control group, sham operation group, HF group, HF + solvent group, HF + levosimendan group, HF + sarcopenia group, HF + sarcopenia + solvent group, HF+ sarcopenia + levosimendan group. After the treatment, exercise capacity and cardiac function were evaluated. Muscle morphology, inflammation level and apoptosis levels were detected, in which mitochondrial function and oxidative stress level were also assessed. Result Levosimendan could increase forelimb grip strength, hanging impulse, maximum running distance and time in mice with HF and sarcopenia (P<0.0001 for all), and these improvements were independent of EF (P=0.0019 for hanging impulse, P<0.001 for forelimb grip strength and maximum running distance). Levosimendan directly increased the CSA of gastrocnemius in mice with HF and sarcopenia (P<0.0001). After levosimendan injection, the proportion of slow muscle fibers increased (P<0.0001), but this improvement of muscle fiber typing might be attributed to improved cardiac function (P>0.05). Levosimendan also maintained mitochondrial membrane potential, decreased cleaved caspase-3 (P=0.034), cleaved caspase-9 (P<0.0001), Bax expression (P<0.0001), and increased Bcl2 expression (P=0.0036). This effect is independent of improved cardiac function (P=0.028 for bax, P<0.001 for cleaved caspase-9 and Bcl2). IL-6, TNF-α expression (P<0.0001 for both) decreased and SOD activity (P=0.0038), GSH/GSSG ratio (P=0.002) significantly increased in skeletal muscle after injection of levosimendan. The improvement in oxidative stress level was attributed to improved cardiac function (P>0.05). Conclusion Levosimendan reduce the loss of skeletal muscle mitochondrial membrane potential, decrease the apoptosis, alleviate the inflammation and oxidative stress, and ultimately improve the exercise capacity of mice with heart failure and sarcopenia. Therefore, levosimendan may be a potential drug for the treatment of heart failure with sarcopenia.